Patogenisitas Jamur Entomopatogen Aschersonia sp. Sebagai Pengendalian Hama Kutu Sisik Citricola Coccus pseudomagnoliarium (Kuw.) (Homoptera : Coccidae) Pada Tanaman Jeruk - Barep Seto Pramono; Hari Purnomo (Fakultas Pertanian Universitas Jember, 2019)
One of the pests that attack the citrus plant is the scales of the citricola scales Coccus pseudomagnoliarium (Homoptera: Coccidae) which attack the branches and branches of the orange plant. This research aims to determine the level of pathogenicity of Aschersonia sp. in controlling C. pseudomagnoliarium pests in citrus plants. This research was conducted by knowing the level of pathogenicity of Aschersonia sp. in C. pseudomagnoliarium pests based on observations of C. pseudomagnoliarium nymph mortality variables, mycosis, mummification, and LC50 values (Lethal Concentration 50) and LT50 (Lethal Time 50). This research can provide information on the pathogenicity of Aschersonia sp. against C. pseudomagnoliarium in citrus plants. The highest percentage of mortality occurred at the treatment density of 109 spores/ml with a value of 77.50% and the lowest percentage of mortality occurred at the treatment density of 105 spores/ml with a value of 15.00%. LC values indicate that the spores density of 2.8 × 107 spores/ml has been able to kill 50% of the test insects, while to kill 90% of the test insects requires a density of 2.4 × 1010 spores/ml and to kill 95% of the test insects requires a density 1.6 × 1011 spores/ml. The LT50 calculation results show that the 1 × 109 spore density treatment has the smallest LT50 value of 3.11 days.